Results of approbation of integrated methods of formation of anti suicidal behavior in adolescence and young adulthood. (Journal of Educational Sciences, 2016)
In the article are part of the materials of the second stage of execution of the grant of MES of RK on the theme “Scientific-theoretical basis and prevention of problems suicide among young people”. In particular theoretically substantiates the necessity of the formation of a anti suicidal person’s behavior and are the results of testing of integrated methods of formation of such behavior in adolescence and young adulthood.The urgency of the problem justifies the increase in the number of suicides among young people and the low effectiveness of the programmers being implemented obstruction of suicide. The need to fight with suicidal incidents and the formation of anti suicidal behavior authors attribute with a absolute value of a human life, tragic senselessness of death, that methodologically confirmed studied concepts and theories. The authors consider the essence and content of the notion «anti suicidal behavior» and а anti suicidal personality factors preventing suicidal behavior. The offered complex methodology of formation anti suicidal behavior in adolescence and young adulthood is represented by seven programs, contents of which are briefly highlighted in the article. A key link in the article are the results of approbation of a comprehensive methodology revealed by the cut-off on a small sample. Slice was based on the use of the Scale of suicidal ideation A. Beck, «Questionnaire anti suicidal motives,Scale and severity of suicidal activity A.G. Аmbrumova (1980), and Visual analogue scales (VAS ). 48 participants slice were divided into two equal groups. The experimental group or «intervention group» were trained initially participated in all major prevention programmers. The control group consisted of students that they worked only in the aspect ofovercoming difficult life situations («individual assistance programmed and the programmed for crisis intervention), i.e., a contingent of the control group were persons having some suicidal tendency. The results helped the authors conclude that prevention programs that have value-semantic value, including restoring or establishing contacts with the family and friends of the participants of the methods is more efficient to reduce thelevel of suicidal activity than programs that do not include these activities and focused on individual work.
Keywords: suicidal behavior; anti suicidal behavior; anti suicidal factors of personality; anti suicidal barrier; comprehensive methodology; prevention; crisis intervention; intervention group; anti vital activity; vital activity